1996
DOI: 10.1104/pp.111.4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Phosphate Synthase Expression at the Cell and Tissue Level Is Coordinated with Sucrose Sink-to-Source Transitions in Maize Leaf

Abstract: lmmunohistological analyses for sucrose phosphate synthase (SPS) show that the protein is localized in both bundle-sheath cells (BS) and mesophyll cells (M) in maize (Zea mays) leaves. I n young leaves, SPS protein was predominantly i n the BS, whereas mature leaves showed nearly equal levels of signal i n both BS and M. A cell-type-specific response was also seen in light and dark treatments. Dark treatments led t o reduced signal in M; however, little or no change was detected in BS. We suggest that SPS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…This is perhaps surprising since based on the distribution of SPS and labeling, it was previously concluded that most of the sucrose (in mature leaves) is synthesized in MCs (Usuda and Edwards, 1980;Lunn and Furbank, 1997). However, a later immunohistological study came to a completely different conclusion and showed that SPS is localized in both BSCs and MCs (Cheng et al, 1996). In fact, in young leaves, SPS protein was predominantly in BSCs, whereas mature leaves showed nearly equal levels of signal in both BSCs and MCs (Cheng et al, 1996).…”
Section: Sink-source Relationships In Primary Carbon Metabolismmentioning
confidence: 98%
“…This is perhaps surprising since based on the distribution of SPS and labeling, it was previously concluded that most of the sucrose (in mature leaves) is synthesized in MCs (Usuda and Edwards, 1980;Lunn and Furbank, 1997). However, a later immunohistological study came to a completely different conclusion and showed that SPS is localized in both BSCs and MCs (Cheng et al, 1996). In fact, in young leaves, SPS protein was predominantly in BSCs, whereas mature leaves showed nearly equal levels of signal in both BSCs and MCs (Cheng et al, 1996).…”
Section: Sink-source Relationships In Primary Carbon Metabolismmentioning
confidence: 98%
“…The protein concentrations were determined using the Bio-Rad DC protein assay kit with BSA as a standard. SuSy activity was measured as the rate of Suc cleavage (Chourey, 1981). The resultant reducing sugars were estimated according to the method of Nelson (1944).…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
“…Immunolocalization was conducted according to the procedure described by Chen and Chourey (1989) and the modifications described by Cheng et al (1996). To avoid physical contamination of the seed sections by fiber due to its softness, the fiber was removed from the remaining seed and treated in parallel.…”
Section: Immunolocalization and Histochemical Stainingmentioning
confidence: 99%
“…The level of SPS activity in source tissues appears to be mainly regulated, at the enzyme level, by allosteric (Doehlert and Huber, 1984) and covalent (Huber and Huber, 1990;Huber and Huber, 1991;Toroser and Huber, 1997) modifications. In contrast with this, the developmental and tissue-specific distribution of SPS has been suggested to be regulated at the transcriptional level (Harn et al, 1993;Klein et al, 1993;Cheng et al, 1996;Valdez-Alarcó n et al, 1996).…”
mentioning
confidence: 99%